1987
DOI: 10.1111/j.1432-1033.1987.tb11213.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and regulation of somatomedin‐C/insulin‐like growth factor I (Sm‐C/IGF‐I) receptors on cultured pig Leydig cells

Abstract: We have characterized somatomedin‐C/insulin‐like growth factor I (Sm‐C/IGF‐I) receptors in cultured pig Leydig cells by binding and cross‐linking affinity experiments. At equilibrium the dissociation constant and the number of binding sites per cell were 1.8 ± 0.2 × 10−9 M and 12200 ± 3200 respectively. Under reducing conditions, disuccinimidyl suberate cross‐linked 125I‐Sm‐C to one receptor complex with apparent Mr= 120000. Continuous treatment of Leydig cells with increasing concentrations of human chorionic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1
1

Year Published

1989
1989
2000
2000

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 49 publications
3
22
1
1
Order By: Relevance
“…It has been shown that cultured rat Sertoli cells produced IGF-I [12], and cultured pig Leydig cells contain specific IGF-I receptor, and IGF-I enhances not only LH receptor, but also the coupling of the receptor to adenylate cyclase [13,14]. No direct effects of GH on testosterone production in isolated Leydig cells have been observed in our study.…”
Section: Discussioncontrasting
confidence: 41%
“…It has been shown that cultured rat Sertoli cells produced IGF-I [12], and cultured pig Leydig cells contain specific IGF-I receptor, and IGF-I enhances not only LH receptor, but also the coupling of the receptor to adenylate cyclase [13,14]. No direct effects of GH on testosterone production in isolated Leydig cells have been observed in our study.…”
Section: Discussioncontrasting
confidence: 41%
“…Concerning the mechanism of GH action, the relevance of IGF-I to testicular function is suggested by many observations indicating that both Leydig and Sertoli cells produce and contain specific IGF-I receptors [25][26][27][28][29] and that IGF-I increases LH receptor and steroidogenic response to hCG in GH-deficient mice [30]. These findings would suggest that GH directly or GH mediated by IGF-I is involved with testicular testosterone action.…”
Section: Discussionmentioning
confidence: 89%
“…I'IGF-I. L'IGF-I augmente ie nombre de r6cepteurs ~t LH/hCG, la production d'AMPc et de testost6rone par la ceilule de Leydig, en r6ponse ~t une stimulation par hCG [5,20]. Les cellules de Sertoli s6cr~tent un peptide qui ales m~mes propri6-t6s physicochimiques et biologiques que I'IGF-I purifi6 humain et I'IGF-I obtenu par g6nie g6n6tique.…”
Section: I'igf-iunclassified